It's a long way to the top: Plant species diversity in the transition from managed to old‐growth forests. (14th December 2017) - Burrascano, Sabina; Ripullone, Francesco; Bernardo, Liliana; Borghetti, Marco; Carli, Emanuela; Colangelo, Michele; Gangale, Carmen; Gargano, Domenico; Gentilesca, Tiziana; Luzzi, Giuseppe; Passalacqua, Nicodemo; Pelle, Luca; et al.
Abstract: Questions: Do vascular plant species richness and beta‐diversity differ between managed and structurally complex unmanaged stands? To what extent do species richness and beta‐diversity relate to forest structural attributes and heterogeneity? Location: Five national parks in central and southern Italy. Methods: We sampled vascular plant species composition and forest structural attributes in eight unmanaged temperate mesic forest stands dominated or co‐dominated by beech, and in eight comparison stands managed as high forests with similar environmental features. We compared plant species richness, composition and beta‐diversity across pairs of stands (unmanaged vs managed) using GLMMs. Beta‐diversity was quantified both at the scale of each pair of stands using plot‐to‐plot dissimilarity matrices (species turnover), and across the whole data set, considering the distance in the multivariate species space of individual plots from their centroid within the same stand (compositional heterogeneity). We modelled the relationship between species diversity (richness and beta‐diversity) and forest structural heterogeneity and individual structural variables using GLMMs and multiple regression on distance matrices. Results: Species composition differed significantly between managed and unmanaged stands, but not richness and beta‐diversity. We found weak evidence that plant species richness increased with increasing levels of structural heterogeneity and canopy diversification. At the scale of individual stands, species turnover was explained by different variables in distinct stands, with variables related to deadwood quantity and quality being selected most often. We did not find support for the hypothesis that compositional heterogeneity varies as a function of forest structural characteristics at the scale of the whole data set. Conclusions: Structurally complex unmanaged stands have a distinct herb layer species composition from that of mature stands in similar environmental conditions. Nevertheless, we did not find significantly higher levels of vascular plant species richness and beta‐diversity in unmanaged stands. Beta‐diversity was related to patterns of deadwood accumulation, while for species richness the evidence that it increases with increasing levels of canopy diversification was weak. These results suggest that emulating natural disturbance, and favouring deadwood accumulation and canopy diversification may benefit some, but not all, facets of plant species diversity in Apennine beech forests. Abstract : The proportion of European forests with a heterogeneous structure is increasing but we still do not know how this affects plant diversity. We found that structurally complex stands have a distinct species composition from that of comparison stands, but neither higher species richness nor beta‐diversity. Deadwood accumulation and canopy diversification had weak positive effects on these facets of plant diversity.